Risk Level of the Factors Affecting Quality in Design Phase of Construction Projects of Sindh - Muhammad Faizan; Memon, Nafees Ahmed; Burki, Faridullah (Tropical Scientific Journal, 2023)
Objective: Implementation of construction project involved several phases and design phase is vital in ensuring the success of the project. Hence, this paper presents the research on identifying the factors affecting quality and assesses the risk level of identified factors in design phase of construction projects of Sindh. Quality in design is the main factor for the success of the construction projects and can be considered as the fulfillment of expectations. Presently, construction industry is paying the utmost attention towards the achievement of quality in construction projects. This paper aims to identify the factors affecting quality and assessed the risk level of identified factors in design phase of construction projects. Research Method: Twenty (20) factors affecting quality of construction projects were identified through the extensive literature review. Questionnaire survey was carried out for data collection to solicit the views of construction practitioners and received the Ninety Seven (97) completed questionnaires which were analyzed statistically. Findings: The results revealed that top five factors which are the most important for improving the quality of construction projects: last minute changes by client, lack of fund for staff job training on quality, insufficient project budget, insufficient overall design time and method of selecting the designer based on lowest price offer. Originality: This research will provide guidance for professional experts in order to achieve the quality during the design phase of construction projects.